B1 lymphocytes and myeloid dendritic cells in lymphoid organs are preferential extratumoral sites of parvovirus minute virus of mice prototype strain expression - Raykov, Zahari Zahariev; Savelyeva, Larissa; Giese, Thomas; Rommelaere, Jean; Giese, Nathalia (Journal of virology, 2005)
Due to their oncolytic properties and apathogenicity, autonomous parvoviruses have attracted significant interest as possible anticancer agents. Recent preclinical studies provided evidence of the therapeutic potential of minute virus of mice prototype strain (MVMp) and its recombinant derivatives. In a murine model of hemangiosarcoma, positive therapeutic outcome correlated with high intratumoral expression of MVMp-encoded genes in tumors and lymphoid organs, especially in tumor-draining lymph nodes. The source and relevance of this extratumoral expression, which came as a surprise because of the known fibrotropism of MVMp, remained unclear. In the present study, we investigated (i) whether the observed expression pattern occurs in different tumor models, (ii) which cell population is targeted by the virus, and (iii) the immunological consequences of this infection. Significant MVMp gene expression was detected in lymphoid tissues from infected tumor-free as well as melanoma-, lymphoma-, and hemangiosarcoma-bearing mice. This expression was especially marked in lymph nodes draining virus-injected tumors. Fluorescent in situ hybridization analysis, multicolor fluorescence-activated cell sorting, and quantitative reverse transcription-PCR revealed that MVMp was expressed in rare subpopulations of CD11b (Mac1)-positive cells displaying CD11c+ (myeloid dendritic cells [MDC]) or CD45B (B220+ [B1 lymphocytes]) markers. Apart from the late deletion of cytotoxic memory cells (CD8+ CD44+ CD62L−), this infection did not lead to significant alteration of the immunological profile of cells populating lymphoid organs. However, subtle changes were detected in the production of specific proinflammatory cytokines in lymph nodes from virus-treated animals. Considering the role of B1 lymphocytes and MDC in cancer and immunological surveillance, the specific ability of these cell types to sustain parvovirus-driven gene expression may be exploited in gene therapy protocols.
Gesehen am 19.02.2021